Methylene blue inhibits the increase of inducible nitric oxide synthase activity induced by stress and lipopolysaccharide in the medial basal hypothalamus of rats - Lomniczi, Alejandro (2000)
In infection bacterial products such as lipopolysaccharides (LPS) induce inducible nitric oxide synthase (iNOS) that produces large quantities of NO toxic to the invading organisms, but also often has toxic effects on host cells. Therefore, inhibition of iNOS activity might be beneficial in combatting these adverse effects. To determine if methylene blue (MB), an oxidizing agent that inactivates iNOS, would reduce the iNOS levels in the medial basal hypothalami (MBH) of conscious male rats, LPS (5 mg/kg) was injected intravenously (i.v.), and after 3 h they were injected i.v. with either MB (3 mg/kg) or saline and the effects on iNOS in the MBH determined. iNOS was measured by conversion of labeled arginine into citrulline by incubating MBH in the absence of calcium (Ca2+) since iNOS does not require Ca2+ for activation. The results indicate that iNOS was induced by the injection of saline, but the induction by LPS was much greater, an increase of 10-fold above that of control sham-operated animals. Both the induction of iNOS from the stress of saline injections and LPS were completely eliminated by MB indicating that MB might be beneficial in preventing injury to brain tissue following LPS injection. There was no effect of either LPS or MB on the Ca2+-dependent constitutive NOS activity. Copyright © 2000 S. Karger AG, Basel.